PENGARUH PENDEKATAN ACTIVE LEARNING TERHADAP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER ISLAMI SISWA SMPN 4 TANJUNGPINANG-KEPULAUAN RIAU - Wirdatul Aini (Jurusan Tarbiyah dan Pendidikan, 2022)
Abstract The study is triggered by the current students’ condition in the Islamic religious education class, which are mostly lack of participation, lack of activeness, and lack of acting with good character. To cope with the problems, this study implemented Active learning in Islamic religious education as a way to shape students’ Islamic characters in SMP N 4 Tanjungpinang, Kepulauan Riau. The research method used is a quantitative method with the type of survey research. The results of calculations from questionnaire data or questionnaire distribution state that there is a positive and significant influence between the X variable